Formulation and evaluation of the efficacy of an artificial larval diet for rearing various species of flies under laboratory conditions - Defilippo, Francesco; Gemmellaro, M. Denise; Grisendi, Annalisa; Tranquillo, Vito; Lavazza, Antonio; Dottori, Michele; Moreno, Ana (Frontiers in Insect Science, 2025)
The larvae of five dipteran species were reared on artificial diets under controlled laboratory conditions. Usually, these species complete their life cycles in perishable, filthy, unhygienic, and foul-smelling natural diets, which hinder rearing work and affect the laboratory environment. More importantly, these unaltered foods do not allow for true conformity in rearing protocols. The addition of a standard artificial diet to rearing protocols would make it possible to conduct ecological, biological, and forensic investigations with greater accuracy and precision. To address this problem, we formulated a new artificial diet for larvae and tested its performance on five different fly species (Calliphora vicina, Lucilia sericata, Sarcophaga argyrostoma, Musca domestica, and Hermetia illucens). We compared the development of larvae reared on an artificial diet with that of larvae reared on beef liver and pig muscle. The results showed no differences in development time between the two groups. However, our results showed that the artificial diet facilitated the rearing of flies for forensic and medical purposes by standardizing the nutritional value of the diet, improving laboratory conditions, and providing a more hygienic and cost-effective food substrate.